2017
DOI: 10.1055/s-0037-1606368
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamics of Labor in Women Undergoing Vaginal and Cesarean Deliveries as Determined by Whole Body Bioimpedance

Abstract: Whole body bioimpedance can be used effectively to assess the hemodynamics of vaginal and cesarean deliveries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Thus far, studies investigating maternal hemodynamics during labor and delivery have yielded conflicting results, especially regarding magnitude and timing of hemodynamic adaptations. Previous studies suggested inconsistent results on the effect of EA on maternal hemodynamics during labor [19,[23][24][25][26]. EA induces a sympathetic blockade that causes vasodilatation and a decrease in venous return to the heart, which can result in maternal hypotension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus far, studies investigating maternal hemodynamics during labor and delivery have yielded conflicting results, especially regarding magnitude and timing of hemodynamic adaptations. Previous studies suggested inconsistent results on the effect of EA on maternal hemodynamics during labor [19,[23][24][25][26]. EA induces a sympathetic blockade that causes vasodilatation and a decrease in venous return to the heart, which can result in maternal hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…However, these effects are seen in only some of the studies and reported clinically in only 0-14% of laboring women receiving EA [23][24][25][26][27]. Recently, Ashwal et al [19] compared maternal hemodynamics following vaginal and cesarean deliveries determined by a whole body bioimpedance-based device. They found a significant decrease in cardiac index and in MAP measured before and after EA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normal vaginal delivery (VD) with epidural analgesia is characterised by a reduction in mean arterial pressure and cardiac index [10]. Elective caesarean section (CS) with epidural anaesthesia at term is associated with significant increases in stroke volume and cardiac output following delivery of the placenta [11].…”
Section: Peripartum and Postpartummentioning
confidence: 99%